Analisis Kebutuhan Tenaga Laboran Pada Laboratorium Teknik Sipil Universitas Negeri Gorontalo (Studi Kasus: Laboratorium Mekanika Tanah) - Kristifiani Sahrain; Fadly Achmad; Yulianti Kadir (Transbahasa, 2025)
This study aims to analyze the need for laboratory assistants based on the actual workload in the Soil Mechanics Laboratory, Civil Engineering Department, Gorontalo State University. The existence of sufficient and qualified laboratory staff is very important to support the implementation of practicum, research, and optimal laboratory services. In this research, the Workload Analysis method is used as the main approach, which consists of several stages: identification of types of activities, measurement of standard time, and calculation of workload based on the volume of annual activities. Data were collected through observations, interviews, and distribution of questionnaires/questionnaires to laboratory assistants. The results of the analysis show that the number of laboratory assistants currently available is not sufficient to meet the ideal workload requirements. Workload calculations show that ideally this laboratory requires at least 4 laboratory assistants with expertise in soil mechanics, while the current number only reaches 2 people. This shortage has an impact on reducing the effectiveness of practicum implementation, potential service delays, and limited technical support for student and lecturer research activities. Therefore, the addition of laboratory assistants and the reorganization of duties and responsibilities are needed to ensure optimal laboratory performance in the future.